Laboratory testing of rivaroxaban in routine clinical practice: When, how, and which assays. (September 2013) - Lindhoff-Last, Edelgard; Ansell, Jack; Spiro, Theodore; Samama, Meyer Michel
Abstract A number of target-specific oral anticoagulants (TSOAs) have been developed in recent years, and some have shown considerable promise in large-scale, randomized clinical trials in the prevention and treatment of thromboembolism. Unlike traditional anticoagulants, such as vitamin K antagonists, these TSOAs exhibit predictable pharmacokinetics and pharmacodynamics. Among these agents, rivaroxaban, a direct Factor Xa inhibitor, has been approved for clinical use in many countries for the management of several thromboembolic disorders. As with the other TSOAs, rivaroxaban is given at fixed doses without routine coagulation monitoring. However, in certain patient populations or special clinical circumstances, measurement of drug exposure may be useful, such as in suspected overdose, in patients with a haemorrhagic or thromboembolic event during treatment with an anticoagulant, in those with acute renal failure, or in patients who require urgent surgery. This article summarizes the influence of rivaroxaban on commonly used coagulation assays and provides practical guidance on laboratory testing of rivaroxaban in routine practice. Both quantitative measurement (using the anti-Factor Xa method) and qualitative measurement (using prothrombin time, expressed in seconds) are discussed, together with some practical considerations when performing these tests and interpreting the test results.